Integrated Farming Systems Management for Sustainable Sericulture: a Case Study - S. Rajadurai; T.M. Veeraiah (Journal of Agricultural Extension Management, 2025)
Integration of crop farming along with livestock, poultry etc., benefit the farmers considerably, in terms of improvement in livelihood. In India, sericulture, a flourishing sector of many farming communities is found profitable and a lucrative monetary venture. Of late, sericulturists have initiated mixed farming of sericulture along with aquaculture, floriculture, horticulture, livestock and poultry and thereby improved their economic condition considerably. Karnataka, a leading state in mulberry sericulture is becoming a model in introducing Integrated Farming Systems in the field of sericulture